2018
DOI: 10.21608/jhiph.2018.19918
|View full text |Cite
|
Sign up to set email alerts
|

Mammography Screening Utilization Behavior among Egyptian Female Employees in Alexandria

Abstract: Background: Breast cancer (BC) has become a health priority due to its increasing incidence. It is curable when detected at an early stage, so there is an urgent need for its early detection. Mammography screening (MS) is the main recommended test for early detection of BC. Objectives: The aim of the study was to assess MS utilization behavior among female employees and to identify some factors based on the Health Belief Model that determines the likelihood of MS utilization behavior in terms of: health belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Additionally, our findings indicated short distances to health facilities increased the odds of BC screening by 3.2. Consistently, these findings concur with Salama [29], Diab, et al [21], and Ondimu [25] who established uptake of BC screening services was higher in women who accessed BC screening services when compared to those who did not. This was attributed to expenses influenced by the distance between the residence and the screening unit.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, our findings indicated short distances to health facilities increased the odds of BC screening by 3.2. Consistently, these findings concur with Salama [29], Diab, et al [21], and Ondimu [25] who established uptake of BC screening services was higher in women who accessed BC screening services when compared to those who did not. This was attributed to expenses influenced by the distance between the residence and the screening unit.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Antabe, [12] had found that women in the highest wealth quantile were 1.33 times more likely to undergo BC screening services compared to those in the lowest wealth quantile. However, research carried out in France and Nigeria found no difference between women with high income and those with low income in regard to uptake of BC screening services [21,22].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation